STEP-NC - Kržič, Primož (Strojniški vestnik, 2009)
The paper deals with the newest advances in standardization of manufacturing data management. The overview of previous work and projects and the latest developments on introducing the ISO 10303- 238 and ISO 14649 standards is presented. The advantages of the new data models are shown and the plans on future work are presented.
Keywords: CNC stroji; ISO standardi; programiranje